Paying for Crimes and Earning Heaven. Daily Life of Imprisoned Women at “El Buen Pastor” Penitentiary 1890-1929. (2015)
During the period of Colombian conservative hegemony, “El Buen Pastor” prison, in Bogotá, provides an illustration of penitentiary politics, as well as the formal and informal mechanisms of social control at the time, gathered in a single institution. In an attempt to reconstruct institutional history, the following article presents the daily practices of female penitentiary coninement through a dialogue between institutionalism and critical criminology, in which criminal law, religion, and social control converge in the same scenario and with the same objective: stopping criminality.